ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PADA USAHA MIKRO KECIL MENENGAH (UMKM) - Tise Lestyawati; Eko Triyanto (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to test the influence of Online Accounting Software, Educational Background, Business Size and MSME Business Duration on the Quality of MSME Financial Statements in Gondangrejo District. The population in this study is MSMEs located in Gondangrejo District, which amounts to 925 MSMEs. From this population, a study sample of 90 respondents was drawn which was confirmed through the Slovin formula. The data obtained are primary data and obtained from the distribution of questionnaires with a total of 35 questions. Each question is measured on five likert scales. The data analysis technique in this study uses multiple linear regression analysis techniques. The results showed that the variables of Online Accounting Software and Business Duration did not have a significant effect on the Quality of MSME Financial Statements in Gondangrejo District. Variables of Education Background and Business Size have a significant effect on the Quality of MSME Financial Statements in Gondangrejo District. Keywords: Online Accounting Software, Educational Background, Business Size, Length of Business, Quality of Financial Statements